เทคโนโลยีกับการต่อสู้ทางการเมืองโดยไร้ความรุนแรง : ศึกษากรณีอินเทอร์เน็ตในประเทศไทย - ชาญชัย ชัยสุขโกศล (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
This dissertation studies the relationship between a nonviolent political movement, socalled ‘nonviolent action’ and a large technological system, ‘the internet’, which are connected by theories of power. While nonviolent action operates via consent power, the internet operates as a site of structural power. The two main research questions are: (1) how can the characteristics and the dynamics of internet-based nonviolent struggle in a Thai case study be explained? (2) how is the internet technological system used as a tool of power by each political player; and whether does it support or suppress nonviolent action? To answers these questions, three issues are investigated in this study: (1) historical development—structural, technical, and institutional—of the Thai internet to understand how the structural power embedded within the internet system during its establishment and expansion phases; (2) web-based struggle of political groups involved in the anti-Thaksin government phenomenon prior to the coup d’ etat on September 19, 2006, including manager.co.th, Radjdumnern webboard of pantip.com/café, midnightuniv.org and prachatai.com; and (3) website intervention and censorship as the entry points of structural power to undermine, technically and institutionally, the capacity of nonviolent movements. Research method employed here are an analysis of primary and secondary resources including from off- and on-line materials and in-depth interviews. The findings on the characteristics and dynamics of web-based nonviolent action are as follows: (1) Three political groups --anti-government, pro-government, and anti-Article 7 groups were involved in the anti-Thaksin government phenomenon. All the three groups could be regarded as nonviolent movements because they did not employ physical violent means while using methods of nonviolent action to handle with the legitimacy or gain consent of other groups. (2) The usage of the internet in the movements could be classified as ‘internet activism’ since the internet was used as a basic communicative instrument. However, the utilization was not yet developed into an advanced level of ‘hacktivism’ (hacker+activism) in the form of ‘electronic civil disobedience’ as appeared in other countries. (3) Methods of nonviolent action used by the three groups mainly focused on protests and persuasion. A number of non-cooperation campaigns were launched and publicized mainly through websites. Nonviolent intervention was also operated by means of disclosing technical information of the other groups’ secret action and ‘culture jamming’, a well-known technique among cyberactivists in the world today. (4) Utilizing the internet in the movements triggered the ‘technological dynamic of nonviolent action’ effect, especially technical and institutional reacting measures from people in power, who also hold technological power. Under this technological dynamic, some action could possibly be developed into ‘technical noncooperation’ and ‘technical nonviolent intervention’. These could be called ‘technical method of nonviolent action’. (5) In conflict situations in which all players employed nonviolent measures, a key factor determining superiority of one player over the others was ‘cyberresource’. This factor would increase ‘quantitative power’ up to the level which enables the player to practice ‘nonviolent containment’ against agenda setting and information of other groups.